Accident prediction based on integrated design consistency with the lower number of vehicles/traffic volumes (due to health disaster/covid-19) - Prasetijo, Joewono; Zhang, Guohui; Isradi, Muhammad; Setiawan, M. Ikhsan; Zainal, ZaffanFarhana; Musa, Wan Zahidah (DOAJ, 2020)
Purpose: Malaysia is one of the developing countries that facing high road accident in Asia. The most common accident happens is between motorcyclist and cars. A motorcyclist is 17 times more dangerous than passenger cars. Analysis shows the three main types of accidents in Malaysia is collision with passenger cars, collisions with other motorcycles and single-motorcycle accidents. Road accidents keep rising in Malaysia, because lacks of road geometric design consistency where the drivers make mistakes errors due to the road geometric features. Design/methodology/approach: The study was conducted at F0050 from km 21 until km 25. By using GPS (DG -200), the continuous speed profile data were using new analysis method to develop road design consistency profile of motorcycle and cars and determined the value of the index the integrated road design consistency (IC). Findings: The developments of consistency model are based on parameter: the bounded area between the profile and the average speed, standard deviation of speed along a segment. Hence, use ACAD software for develops consistency model’s profile. The integrated-consistency model is the impact of the speed profile on design consistency in traffic and safety evaluations. The highest areas of an accident at km 24 are justified based on the design consistency of the area and integrated design consistency model between of car and motorcycle is poor design. The study shows that crashes and fatalities are fully effected by traffic volumes but road design performances and driving behaviour. Research limitations/implications: However, the traffic volumes are relatively low at the whole country regarding to the Movement Control Order (MCO) due to the pandemic COVID-19 since March 2020. In contrast with the reduction of the volumes, number of crashes still shows relatively high. Therefore, it shows that crashes and fatalities are influenced by other factors. Geometric factors such as access point, tangent length, curve length, shoulder width and lane width are influencing for an operating speed profile for a developed of tangents and curves of motorcycle and cars. Practical implications: Result of this study can be used as references to solve accident problems in Malaysia. Paper type: This study is categorised as a case study.